2001
DOI: 10.1034/j.1399-3054.2001.1130213.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of Pinus halepensis needles under ozone and water stress conditions

Abstract: The aim of this study was to evaluate how physiological processes of potted Pinus halepensis plants, grown under controlled conditions, were affected by ozone (O3) and/or water stress, integrating the gas exchange and biochemical data with fluorescence OJIP polyphasic transient data. Plants submitted to only water stress (T1) and with ozone (T3) showed a strong decrease in stomatal conductance and gas exchange, coinciding with a reduction of maximum yield of photochemistry (varphipo) and very negative values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…On the other hand, Manes et al (2001) showed a complex relationship between ozone stress and water stress using the potted P. halepensis Mill. They showed that ozone stress with water stress decreased gl but that ozone stress without water stress decreased the activity of the Calvin cycle.…”
Section: Physiological Relationshipsmentioning
confidence: 98%
“…On the other hand, Manes et al (2001) showed a complex relationship between ozone stress and water stress using the potted P. halepensis Mill. They showed that ozone stress with water stress decreased gl but that ozone stress without water stress decreased the activity of the Calvin cycle.…”
Section: Physiological Relationshipsmentioning
confidence: 98%
“…Though decreasing conductance is a common response to O 3 exposure, many studies demonstrate that conductance and transpiration rates can also increase after chronic O 3 exposure (Freersmith and Dobson 1989;Maiermaercker and Koch 1991;Manes et al 1998Manes et al , 2001McLaughlin et al 2007;Mills et al 2009) due to functional changes in stomata and stomatal signaling. For example, O 3 has been reported to cause stomata to respond sluggishly to stimuli, resulting in higher integrated daily transpiration rates (Paoletti 2005).…”
Section: Introductionmentioning
confidence: 96%
“…In Wittig et al (2007)'s metaanalysis of tree responses to O 3 compared to ambient background air, O 3 caused an average stomatal conductance decrease of 6% compared to an 18% decrease in photosynthesis. Several studies suggest that decreases in conductance are a secondary response to chronic O 3 exposure and only occur following a reduction in carboxylation efficiency (Farage et al 1991;Manes et al 2001;Noormets et al 2001;Paoletti and Grulke 2005;Paoletti et al 2007;Reich 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other responses, Paoletti et al (2004), Manes et al (2001) and Nussbaum et al (2001) observed a reduction in φPo (Eqn. 7).…”
Section: Quantum Efficienciesmentioning
confidence: 99%